Kinetic study of microalgae biomass growth for tertiary treatment of palm oil mill effluent (POME) - Wun, Wee Long; Tan, See Ying; Chua, Gek Kee; Chin, S. Y.; N., Zainol (School of Engineering, Taylor's University & IChemE, 2014)
In recent years, microalgae have been used to polish Palm Oil Mill Effluent (POME) from the conventional ponding treatment system. The substantial amount of inorganic nutrient and trace metal in POME is believed to encourage the growth of microalgae. The present research studied the kinetic of microalgae mixed culture in treating POME. 10% v/v of microalgae was cultured in 10-100% v/v autoclaved and centrifuged POME in conical flask under light irradiance of 6000 Lux. The supernatant of microalgae mixed culture was collected for BOD and colour (ADMI) determination. The results revealed that the mixed microalgae achieved the highest growth rate of 1.39 d-1 at 30%v/v of POME at the minimum light penetration of approximately 2000 Lux. The corresponding biomass productivity was 0.61 g/L.d. A significant removal of BOD with efficiency of 50%-55% was obtained. Nevertheless, the colour removal efficiency was less than 20%,indicating that the microalgae are not effective in removing colour compound in POME>